"As Natural as the Air Around Us": On the Origin and Development of the Concept of Structural Violence in Health Research. (October 2018) - De Maio, Fernando; Ansell, David
This article examines the concept of "structural violence." Originating in the work of Johan Galtung in 1969 and popularized by Paul Farmer, structural violence is increasingly invoked in health literature. It is a complex concept – rich in its explanatory potential but vague in its operational definition and arguably limited in its theoretical precision. Its potential lies in the focus it gives to the deep structural roots of health inequities; in contrast to the more passive term "social determinants of health, " structural violence explicitly identifies social, economic, and political systems as the causes of the causes of poor health. It is also evocative in its framing of health inequities as an act of violence. Yet the formulation of structure used in this literature is largely atheoretical and, by extension, apolitical. Development of the concept hinges on clarifying the precise aspects of structure it points to (perhaps through using the concept in conjunction with larger theoretical frameworks) as well as improving operational definitions to enable its use in quantitative social epidemiology. We argue that the concept of structural violence can provide a useful lens for understanding health inequities, but its full potential is only realized when combined with larger theoretical frameworks.